How does restaurant's symbolic design affect photo-posting on instagram? The moderating role of community commitment and coolness. Issue 1 (2nd January 2021) - Apaolaza, Vanessa; Paredes, Mario R.; Hartmann, Patrick; D'Souza, Clare
ABSTRACT: The present study analyzes the influence of a restaurant's symbolic design on photo-posting behavior on Instagram. Data from 272 consumers who had visited a restaurant for dinner were used to test the proposed conceptual framework. Results confirmed a positive influence of a restaurant's symbolic design on consumers' photo-posting behavior, mediated by positive emotional arousal. This effect was stronger for individuals with a higher level of commitment to the Instagram community and for those who experienced a greater gratification from being perceived as cool by their peers when posting photos on Instagram. The study contributes to the hospitality marketing management and social media literature by adding to our understanding of the underlying mechanisms that influence user-generated content on Instagram in the restaurant industry. Theoretical contributions and managerial implications are discussed.